STRATEGI PENINGKATAN PRODUKSI PADI OLEH DINAS PERTANIAN KABUPATEN SIAK - Silvia Andriani; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The majority of the people of Kec. Bunga Raya are in the agricultural and plantation sectors. The Siak Regency Agriculture Service makes a special strategy for increasing rice production because the Bunga Raya Sub-district has good production, namely through a program to increase rice production. The purpose of this study was to find out the Strategy of the Implementation of the Rice Production Improvement Program by the Siak Regency Agricultural Service and the inhibiting factors for increasing rice production. The research uses strategy theory concepts according to Elitan in (2008: 9) that have staretgi technology indicators, innovation strategies, operating strategies. This research method uses a qualitative method of case study approach, with data collection techniques including: observation, interviews, and documentation. Research informants were selected through a purposive sampling technique. The research results show that the implementation of the program to increase the production of the Department of Agriculture in Siak district is quite good because of the increased production and fulfillment of the needs of Siak Regency even though in 2017 there was a decline due to the attack of pests that had not been found. The inhibiting factors in increasing rice production in Siak Regency are human resources, community knowledge and infrastructure. control. It is better if the government provides ppl for one village and repairs the irrigation system which still uses old methods that depend on rain and farmers are expected to have the ability to choose good and superior seed quality to produce good production. Keywords: Strategy, Program Implementation, Rice Farmers.